Analisis Sektor Ekonomi Unggulan dan Pergeseran Pertumbuhan Ekonomi di Kabupaten Ponorogo 2015-2019 - Pertiwi, Dea Citra; Hidayat, Wahyu (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2022)
The central government issued Laws No 32 and 33 2004 to carry out regional autonomy as best as possible. With regional autonomy, regions are required to develop the potential of their respective regions as capital for regional development. So the regions are expected to have and improve their abilities in managing the economic potential in their regions without waiting for assistance from the center. This study aims to see the regional economic potential that has a leading sector in increasing growth in Ponorogo Regency. This study uses GRDP data on the basis of 2010 constant prices 2015-2019, Ponorogo Regency and East Java Province. The analysis tools used are Static Location Quotient (SLQ) Analysis, Dynamic Location Quotient (DLQ), Classical Shift Share Analysis and Estaban-Marquilas (SS-EM) Shift Share Analysis. From the combined calculation of SLQ DLQ, which is the basic sector in the superior category is the Construction sector, Real Estate Sector, Education Service Sector, Other Service Sectors. Sectors that have a competitive advantage but are also specialized are the Agriculture, Forestry and Fisheries sectors; Information and Communication sector; Financial Services and Insurance sector; Real Estate sector; Government Administration, Defense and Compulsory Social Security sector; education services sector; the Health Services and Social Activities sector; other service sectors.